2017
DOI: 10.1530/eje-17-0446
|View full text |Cite
|
Sign up to set email alerts
|

Roles of increased glycaemic variability, GLP-1 and glucagon in hypoglycaemia after Roux-en-Y gastric bypass

Abstract: ObjectiveRoux-en-Y gastric bypass (RYGB) surgery is currently the most effective treatment for diabetes and obesity. An increasingly recognized and highly disabling complication of RYGB is postprandial hypoglycaemia (PPH). The pathophysiology of PPH remains unclear with multiple mechanisms suggested including nesidioblastosis, altered insulin clearance and increased glucagon-like peptide-1 (GLP-1) secretion. Whilst many PPH patients respond to dietary modification, some have severely disabling symptoms. Multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 40 publications
4
52
1
4
Order By: Relevance
“…Among others, Abrahamsson et al have reported positive outcomes during treatment with GLP‐1 analogues, including improved glycaemic control and reduced number of patient‐reported hypoglycaemic episodes. In the present study, treatment with liraglutide did not reduce hypoglycaemia nor hyperglycaemia during the MMTTs; however, it led to significant reductions in glucose values below fasting levels, suggestive of a blood glucose‐stabilizing effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among others, Abrahamsson et al have reported positive outcomes during treatment with GLP‐1 analogues, including improved glycaemic control and reduced number of patient‐reported hypoglycaemic episodes. In the present study, treatment with liraglutide did not reduce hypoglycaemia nor hyperglycaemia during the MMTTs; however, it led to significant reductions in glucose values below fasting levels, suggestive of a blood glucose‐stabilizing effect.…”
Section: Discussionmentioning
confidence: 99%
“…A liquid meal (Fresubin Energy Drink, 300 kcal; Fresenius Kabi, Bad Homburg, Germany), consisting of 50% carbohydrates, 35% fat and 15% protein, was consumed at time 0 over a period of 15 minutes. The test meal was chosen based on its comparability with meals used in similar studies . Blood samples were collected at times −20, −10, 0, 5, 10, 20, 30, 45, 60, 90, 120, 150 and 180 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the pancreas, predominant expression of proconvertase 2 leads to preproglucagon processing to produce glucagon. Although some studies have reported an increase in postprandial glucagon after RYGB, a later study suggested that this work was confounded by the fact that RYGB causes large increases glicentin, another preproglucagon peptide that has increasing cross‐reactivity with standard glucagon enzyme‐linked immunosorbent assays with increasing plasma concentrations . Thus, more research is needed from independent groups utilising sensitive and specific assays to determine whether glucagon is increased with surgery or not.…”
Section: Mechanisms For Metabolic Successmentioning
confidence: 99%